Efek pemberian α-tokoferol terhadap jumlah sel spermatogenik dan sel Leydig pada tikus putih (Rattus norvegicus) yang dipapar 2,3,7,8 Tetrachlorodibenzo-p-dioxin - Machmudia, Ainun; Eliyani, Hana; Widjiati, Widjiati; Wurlina, Wurlina (Ovozoa: Journal of Animal Reproduction, 2021)
This research aimed to determine the effect of α-tocopherol on the count of spermatogenic and Leydig cells in rats (Rattus norvegicus) exposed to 2,3,7,8 tetrachlorodibenzo-p-dioxin (dioxin). Dioxin is an endocrine-disrupting agent that adversely affects reproductive health, while α-tocopherol maintains fertility. This research used 25 rats aged 10-12 weeks weighing 150-200 grams. Rats were divided into five groups (K, P0, P1, P2 and P3). The K (control group) was administered with corn oil 1 ml/day. P0 was exposed to 700 ng/kg/day dioxin. P1, P2 and P3 was exposed to dioxin at a dose of 700 ng/kg/day and administered with α-tocopherol at a dose of 77, 140 and 259 mg/kg/day respectively. Dioxin exposure, corn oil and α-tocopherol administration were conducted orally for 20 days. On day-21, all rats were sacrificed for histological slides preparation of testicles with hematoxylin-eosin staining. Data were analyzed with analysis of variance and continued with the Duncan test. The results indicated that exposure to dioxin caused a decrease in the number of spermatogenic and Leydig cells. The administration of α-tocopherol at a dose of 140 mg/kg/day eliminated the effect of reducing the number of spermatogenic and Leydig cells caused by exposure to dioxin. The conclusion was the administration of α-tocopherol at 140 mg/kg/day was effective in maintaining the number of spermatogenic and Leydig cells in rats (Rattus norvegicus) exposed to 2,3,7,8 tetrachlorodibenzo-p-dioxin.